Patterns of Care and Clinical Outcomes of First‐Line Trastuzumab‐Based Therapy in HER2‐Positive Metastatic Breast Cancer Patients Relapsing After (Neo)Adjuvant Trastuzumab: An Italian Multicenter Retrospective Cohort Study. (22nd June 2015) - Lambertini, Matteo; Ferreira, Arlindo R.; Poggio, Francesca; Puglisi, Fabio; Bernardo, Antonio; Montemurro, Filippo; Poletto, Elena; Pozzi, Emma; Rossi, Valentina; Risi, Emanuela; Lai, Antonella; Zanardi, Elisa; et al.
Abstract : Background: We evaluated the patterns of care and clinical outcomes of metastatic breast cancer patients treated with first‐line trastuzumab‐based therapy after previous (neo)adjuvant trastuzumab. Materials and Methods: A total of 416 consecutive, HER2‐positive metastatic breast cancer patients who had received first‐line trastuzumab‐based therapy were identified at 14 Italian centers. A total of 113 patients had presented with de novo stage IV disease and were analyzed separately. Dichotomous clinical outcomes were analyzed using logistic regression and time‐to‐event outcomes using Cox proportional hazards models. Results: In the 202 trastuzumab‐naïve patients and 101 patients with previous trastuzumab exposure, we observed the following outcomes, respectively: overall response rate, 69.9% versus 61.3% (adjusted odds ratio [OR], 0.62; p = .131), clinical benefit rate, 79.1% versus 72.5% (adjusted OR, 0.73; p = .370), median progression‐free survival (PFS), 16.1 months versus 12.0 months (adjusted hazards ratio [HR], 1.33; p = .045), and median overall survival (OS), 52.2 months versus 48.2 months (adjusted HR, 1.18; p = .404). Patients with a trastuzumab‐free interval (TFI) <6 months, visceral involvement, and hormone receptor‐negative disease showed a worse OS compared with patients with a TFI of ≥6 months (29.5 vs. 48.3 months; p = .331), nonvisceral involvement (48.0 vs. 60.3 months; p = .270), and hormone receptor‐positive disease (39.8 vs. 58.6 months; p = .003), respectively. Conclusion: Despite the inferior median PFS, trastuzumab‐based therapy was an effective first‐line treatment for patients relapsing after (neo)adjuvant trastuzumab. Previous trastuzumab exposure and the respective TFI, type of first site of disease relapse, and hormone receptor status should be considered in the choice of the best first‐line treatment option for HER2‐positive metastatic breast cancer patients. Implications for Practice: A paucity of data is available outlining the clinical outcomes of patients who receive trastuzumab as a part of their (neo)adjuvant treatment and then resume trastuzumab‐based therapy in the metastatic setting. In the present study, despite an inferior median progression‐free survival, trastuzumab‐based therapy was shown to be an effective first‐line treatment for patients relapsing after (neo)adjuvant trastuzumab. Previous trastuzumab exposure, the respective trastuzumab‐free interval, the type of first site of disease relapse, and hormone receptor status should be considered in choosing the best first‐line treatment option for HER2‐positive metastatic breast cancer patients. Abstract : The patterns of care and clinical outcomes of metastatic breast cancer patients receiving first‐line trastuzumab‐based therapy after previous trastuzumab therapy were evaluated. Trastuzumab‐based therapy was an effective first‐line treatment for patients with relapse after previous trastuzumab therapy. Various factors, such as trastuzumab‐free interval, type of first site of disease relapse, and hormone receptor status, should be considered in the choice of the best first‐line treatment option for HER2‐positive metastatic breast cancer patients.